PRE-INVESTMENT PROTECTION IN CONNECTION WITH SHARIAH LAW UNDER INTERNATIONAL INVESTMENT LAW - ABADIKHAH Mostafa (Правовое государство: теория и практика)
The territory of an Islamic state is governed by Shariah law. It means every economic operation by national or non-nationals like investment process in an Islamic state’s territory have to be considered from the point of view of Shariah law. In this direction, on the one hand, it is important to be informed regarding Shariah law flowing in host Islamic states at preinvestment stage. On the other hand, drawing a precise framework of the position of Sharia in the territory of the Islamic State is considered a type of pre-investment protection. One of these pre-investment protections is investment guides which is published every year by origin or host states to depict the investment environment of the host state. Purpose: In this article, I am going to analyze the investment guides and answer the main question, how much have investment guides paid attention to Sharia law in the host Islamic state? Methods: general scientific methods of theoretical knowledge, as well as general logical methods and research techniques are used in analyzing existing investment guides of Islamic and non-Islamic states. Results: the present article has come to the conclusion that, the Islamic states hosting foreign investments, like many Arab states in the Middle East, have explained the dimensions and effects of Sharia law in the direction of foreign investment process better than the origin states. In addition, the origin states’ attention to Sharia law depends on the legal system governing the investment host Islamic state.